Quantifying the impact of precipitation fluctuations on forest growth in Northeast China - Hai, Yue; Han, Tian; Wang, Yu; Li, Ruonan; Yang, Yanzheng; Wen, Zhi; Zheng, Hua (Frontiers in Plant Science, 2025)
IntroductionIn the context of climate change, the escalating frequency of global precipitation fluctuations amplifies uncertainties in assessing the impact on forest ecosystem productivity. Hence, elucidating the dynamic relationship between precipitation characteristics and forest growth can provide effective management strategies for addressing climate change.MethodsThis study utilizes precipitation data from 1982 to 2022 to construct the frequency and amplitude of precipitation fluctuations and analyzes the response of forest growth in northern China to these precipitation variations.ResultsThe growth of 13.7% of the region's forest is declining, with 8.1% of the area showing significant degradation. The core degradation zones for forest growth are located in semi-arid regions with precipitation frequencies ≥ 12 and amplitudes ≤ 60 mm and subhumid regions with precipitation frequencies ≥ 14 and amplitudes ≤ 65 mm. In the core semi-arid zone, deciduous broadleaf shrublands have greatest degraded area (2.8×104 ha), but deciduous needleleaf forests have the highest proportion of degradation (57.1%), while in the subhumid core degradation zone, deciduous broadleaf forests have the highest area (1.7×105 ha) and proportion of degradation (9.3%).DiscussionThis study not only provides a novel perspective for evaluating forest ecosystem responses to precipitation characteristics, but also offers crucial theoretical support for advancing the implementation of Nature-based Solutions in practical applications.